PWE-020 Do Seasonal Trends in Positivity Exist with the Guaiac-Based Faecal Occult Blood Test?. (4th June 2013) - Seaman, H E; Butler, P; Snowball, J M; Halloran, S P
Abstract : Introduction: Several bowel cancer screening programmes, including the NHS Bowel Cancer Screening Programme (BCSP) in England, use a guaiac-based faecal occult blood test (gFOBt). Seasonal variations in gFOBt positivity have been reported, with lower positivity in the warmer spring and summer months compared with autumn and winter. As more population-based bowel cancer screening programmes are being planned and implemented worldwide, it is important to highlight the factors that could affect the performance of faecal occult blood tests. Methods: Men and women aged 60–69 years are eligible for biennial routine bowel cancer screening by the BCSP. The gFOBt card comprises six windows (or 'spots') onto which the screening participant is asked to apply two samples from three separate stools. Test cards are returned to one of five BCSP Hubs where each spot is tested to determine 'spot positivity'. The number of positive spots determines test positivity: 5–6 positive spots = positive test and immediate referral for colonoscopy; 1–4 positive spots = weak positive and re-test. Ultimately, a definitive test result is achieved for each screening episode, according to a well-defined test/re-test algorithm. Data from the Bowel Cancer Screening System (BCSS) for the BCSP Southern Hub for April 2008 to March 2012 were analysed and gFOBt spot positivity patterns assessed by month, stratified by age and sex. Analysis was limited to the first (prevalent) screening episode for all individuals. Results: In total, 7, 765, 282 spots were analysed (nearly 1.3 million kits). As expected, throughout the study period, gFOBt spot positivity for men (2.6%) was consistently higher than for women (1.7%) and increased with age. Any variations in seasonal positivity were similar for men and women and all ages. The pattern of spot positivity by month was not consistent year on year and there was no clear evidence that spot positivity was different in the spring/summer months compared with autumn/winter. Conclusion: Seasonal variation did not appear to account for the fluctuations in spot positivity observed. We conducted a sub-group analysis restricted to 60 year-olds to explore the possibility that changes in the demographics of participants over time might affect the positivity patterns, but the data yielded similar inconsistencies. It is unlikely that operational factors account for the fluctuations as the BCSP ensures rigorous monitoring of test kit batches and quality control in the laboratories. More work is required to explore these data further in search of an explanation. Disclosure of Interest: None Declared.